2010
DOI: 10.1007/s11214-010-9637-z
|View full text |Cite
|
Sign up to set email alerts
|

HED Meteorites and Their Relationship to the Geology of Vesta and the Dawn Mission

Abstract: Howardite-e ucrite-diogenite (HED) meteorites, thought to be derived from 4 Vesta, provide the best sampling available for any differentiated asteroid. However, deviations in oxygen isotopic composition from a common mass-fractionation line suggest that a few eucrite-like meteorites are from other bodies, or that Vesta was not completely homogenized during differentiation. The petrology and geochemistry of HEDs provide insights into igneous processes that produced a crust composed of basalts, gabbros, and ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
191
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 201 publications
(198 citation statements)
references
References 121 publications
6
191
1
Order By: Relevance
“…Diogenites material originated from a plutonic layer deep in Vesta's lower crust/upper mantle (McSween et al 2010) and it has been suggested that the lack of this mineralogy among the V-type asteroids could be due to the difficulty in excavating large fragments from depths (Moskovitz et al 2010;Burbine et al 2009). However, numerical simulations (Asphaug 1997) of the South Pole crater formation have shown that a large fraction of the excavated material would have come from Vesta's mantle and not its crust, because it has a diogenite-dominated composition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diogenites material originated from a plutonic layer deep in Vesta's lower crust/upper mantle (McSween et al 2010) and it has been suggested that the lack of this mineralogy among the V-type asteroids could be due to the difficulty in excavating large fragments from depths (Moskovitz et al 2010;Burbine et al 2009). However, numerical simulations (Asphaug 1997) of the South Pole crater formation have shown that a large fraction of the excavated material would have come from Vesta's mantle and not its crust, because it has a diogenite-dominated composition.…”
Section: Resultsmentioning
confidence: 99%
“…A close connection between asteroid (4) Vesta and these basaltic achondrites was established during the earliest studies, including visible and infrared spectroscopic investigations (McCoord et al 1970;McFadden et al 1977;Xu et al 1995;Burbine et al 2001), numerical and dynamical simulations (Asphaug 1997), and spatial resolved observations ; Thomas et al 1997). However, recent studies in oxygen isotopic composition from a common mass-fractionation line suggest that a few eucrite-like A&A 533, A77 (2011) meteorites come from other bodies, or that (4) Vesta was not completely homogenized during differentiation (McSween et al 2010). It is noteworthy that a laboratory analysis of iron meteorites also indicates an origin from at least 70 distinct differentiated parent bodies (Mittlefehldt et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…One of the efforts of the Dawn Science Team has been to investigate the geology of asteroid Vesta through geologic mapping. Geologic mapping attempts to decipher the evolution of a given body (e.g., Coradini et al, 2011;Greeley and Batson, 1990), to provide the context for the spectrally derived composition of the surface (e.g., De Sanctis et al, 2012a), and, in the case of Vesta, to understand the possible link with achondrite meteorites (e.g., McSween et al, 2011;Mayne et al, 2010;Sykes and Vilas, 2001). The first Dawn observations of Vesta's shape and morphology were reported by Jaumann et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…The source of this additional heat may have been from large impacts (Nyquist et al, 1986), heating at depth after burial of surface basalts (Yamaguchi et al, 1996(Yamaguchi et al, , 1997, or the differentiation into layers (Takeda, 1997). A large impact crater of 460 km diameter, 13 km depth with a large central peak, has been identified on Vesta (Thomas et al, 1997) which may have extended beyond the crust into the mantle layer and ejected many Vestoids and HEDs (McSween et al, 2010). The age of this impact crater is controversial, with some evidence suggesting it occurred during the Late Heavy Bombardment period of 3.5-4.0 billion years ago (Scott et al, 2009b), and other evidence supporting an age of only 1 billion years (Asphaug, 1997).…”
Section: Introductionmentioning
confidence: 99%